Psychology of music - Stewart, Effie L. (My University, 1905)
Introduction: There are many beautiful arts today and many which are perhaps more highly developed than music, but to my mind music as an art is the most beautiful and touches the hearts of more people than any other one art. In this work I wish to use the term music in its broadest sense and for a working definition, I will say that any sound or modulation of sounds which is pleasing to the ear, is music. From this use of the term we can say that music in some form has existed since the creation of man. The first music then was the music of nature and from this music, musical instruments were invented. The poets have written of the "sighing of the wind", "lowing of cattle", "chirping of crickets", of the deep voices of the ocean, etc., and some think this merely a fancy of poets, and yet, how many there are of us who enjoy going into the, woods and sitting down under the trees listen to the wind as it whistles and sighs through the leaves, or on a still summer evening do we not enjoy going into the country and listening to the crickets, katydids, and frogs? Some may say this is not music but I think it truly is. have never been fortunate enough to the near the ocean, but have talked with many who have and they always express a longing to be near it again, but it is almost invariably for the roar or music of the ocean rather than the beauty of the great expanse itself. I have heard a few persons say that the roar of the ocean is more to them even than the beautiful scenery of the mountains and they say, while they miss the mountains, they do not fill the place in their hearts that the ocean does.
Citation: Stewart, Effie L. Psychology of music. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Music's Influence; Physically, Mentally, Morally; Music's Power; Music and Love; Theses